2010
DOI: 10.1111/j.1745-4557.2009.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Olive Oil Adulteration With Rapeseed and Sunflower Oils Using Mos Electronic Nose and Smpe‐ms

Abstract: The study analyzed the effectiveness of two types of electronic nose systems to detect adulteration of extra virgin olive oil (EVOO) with rapeseed and sunflower oils. Tested methods included volatile analysis with the electronic nose based on MOS sensors (HS‐E nose) and by direct coupling of SPME to MS (SPME‐MS). Volatile compounds were analyzed also by SPME‐GC/MS. Samples of EVOO were mixed with different proportions, ranging from 5 to 50% (v/v), of seed oils and fingerprints of volatile profiles of all sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Volatile compounds were identified by the SPME-GC/MS technique. The same techniques (HS-E nose, SPME-MS, and SPME-GC/MS) were also applied to detect adulteration of olive oil with rapeseed and sunflower oils (Mildner-Szkudlarz and Jeleń 2010). In both studies, PCA and PLS analyses were applied to the data from two e-noses and chromatographic analyses.…”
Section: Plant Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Volatile compounds were identified by the SPME-GC/MS technique. The same techniques (HS-E nose, SPME-MS, and SPME-GC/MS) were also applied to detect adulteration of olive oil with rapeseed and sunflower oils (Mildner-Szkudlarz and Jeleń 2010). In both studies, PCA and PLS analyses were applied to the data from two e-noses and chromatographic analyses.…”
Section: Plant Oilsmentioning
confidence: 99%
“…In both studies, PCA and PLS analyses were applied to the data from two e-noses and chromatographic analyses. The authors reported that all methods of oil aroma analysis allowed discrimination between non-adulterated and adulterated samples and detection of different contents (5-50% v/v) of hazelnut, rapeseed, and sunflower oil adulterants in olive oil (MildnerSzkudlarz and Jeleń 2008;Mildner-Szkudlarz and Jeleń 2010). When HS-E nose data were used, the PLS model predicted hazelnut adulteration of virgin olive oil with a correlation coefficient of 0.997 and an accuracy of 2.85% (MildnerSzkudlarz and Jeleń 2008), rapeseed oil adulteration with a correlation coefficient of 0.989 and an average error of 4.41%, and sunflower oil adulteration with a correlation coefficient of 0.990 and an average error of 4.20% (Mildner-Szkudlarz and Jeleń 2010).…”
Section: Plant Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are recognized as good alternatives to sensitive laboratory-based techniques in some situations [18]. Sensors like electronic noses [19][20][21] and thin film based chips [22] have been reported for identification and classification of vegetable cooking oils. Nanomaterials such as gold nanoparticles [23], quantum dots [24], and carbon-based nanomaterials [25] have been investigated in biosensing strategies to enhance target recognition, amplify the signal, and improve the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…This multivariate method has been extensively employed for studies on food volatiles (Jabalpurwala et al, 2009;Elaissi et al, 2010;Giri et al, 2010;Mildner-Szkudlarz & Jelen;Zhang et al, 2010). But regarding to insects, PCA has been employed only to study the volatiles of Hymenopteran species (Steiner et al, 2007;Coppee et al, 2008).…”
Section: Viii1 Introductionmentioning
confidence: 99%